2015
DOI: 10.1039/c4nj01435a
|View full text |Cite
|
Sign up to set email alerts
|

Fluorous-inorganic hybrid dielectric materials for solution-processed electronic devices

Abstract: Fluorous-inorganic hybrid dielectric (FIHD) materials in fluorous solvents can be deposited on top of organic semiconductor films by solution casting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…When transferring aggregates from aqueous solution to a thin film, a dramatic change in the dielectric constant (κ) of the surrounding environment occurs (κ: water 80, air ∼1), which can destabilize self-assembled structures . Perfluorocarbons are the most gas-like phase having very low κ (perfluorohexane: 1.57); therefore, we expect aggregates of 2 to easily transfer to surfaces. , Indeed, a simple dropcasting procedure resulted in the transfer of aggregates of 2 to glass with similar absorption and emission profiles to that observed in fluorous solvent (Figures A and S11). Contact angle measurements indicated that the surface was hydrophobic after dropcasting 2 (Figure B).…”
mentioning
confidence: 94%
“…When transferring aggregates from aqueous solution to a thin film, a dramatic change in the dielectric constant (κ) of the surrounding environment occurs (κ: water 80, air ∼1), which can destabilize self-assembled structures . Perfluorocarbons are the most gas-like phase having very low κ (perfluorohexane: 1.57); therefore, we expect aggregates of 2 to easily transfer to surfaces. , Indeed, a simple dropcasting procedure resulted in the transfer of aggregates of 2 to glass with similar absorption and emission profiles to that observed in fluorous solvent (Figures A and S11). Contact angle measurements indicated that the surface was hydrophobic after dropcasting 2 (Figure B).…”
mentioning
confidence: 94%
“…39 Therefore, it is necessary to prepare high dielectric constant composites. A general method is to incorporate ceramic fillers with high dielectric constant (e.g., BaTiO 3 , 4,10–13 SiC, 14 KTa 1−x NbxO 3 , 15 and ZrO 2 16 ) into polymers. However, due to the lack of interaction groups between ceramic fillers and matrix, the ceramic filler cannot ensure its uniform and stable dispersion of ceramic filler in the matrix, which will inevitably create defects in the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The direct photopatterning of BTO thin films was achieved via electron-beam (e-beam) lithography and photolithography. While the preparation of nanoparticles capped with fluorous moieties has been achieved through various methods [29][30][31], in this study, BTO nanoparticles with highly fluorinated ligands were obtained using ligand-exchange reactions [32,33]. To impart solubility to the synthesized BTO nanoparticles (BTO-DA) in a fluorous solvent, perfluoro-3,6,9-trioxatridecanoic acid (PECA) (Fluorochem, Hadfield, UK)-a perfluoroalkyl ether-type ligand functionalized with a carboxylic acid group at the end of the chain-was used to substitute the organic capping ligand surrounding the inorganic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%